Diesel exposure suppresses natural killer cell function and resolution of eosinophil inflammation: a randomized controlled trial of exposure in allergic rhinitics. Issue 1 (December 2015) - Pawlak, Erica; Noah, Terry; Zhou, Haibo; Chehrazi, Claire; Robinette, Carole; Diaz-Sanchez, David; Müller, Loretta; Jaspers, Ilona
Abstract Exposure to diesel exhaust (DE) is known to exacerbate allergic inflammation, including virus-induced eosinophil activation in laboratory animals. We have previously shown that in human volunteers with allergic rhinitis a short-term exposure to DE prior to infection with the live attenuated influenza virus (LAIV) increases markers of allergic inflammation in the nasal mucosa. Specifically, levels of eosinophilic cationic protein (ECP) were significantly enhanced in individuals exposed to DE prior to inoculation with LAIV and this effect was maintained for at least seven days. However, this previous study was limited in its scope of nasal immune endpoints and did not explore potential mechanisms mediating the prolonged exacerbation of allergic inflammation caused by exposure to DE prior to inoculation with LAIV. In this follow-up study, the methods were modified to expand experimental endpoints and explore the potential role of NK cells. The data presented here suggest DE prolongs viral-induced eosinophil activation, which was accompanied by decreased markers of NK cell recruitment and activation. Separate in vitro studies showed that exposure to DE particles decreases the ability of NK cells to kill eosinophils. Taken together, these follow-up studies suggest that DE-induced exacerbation of allergic inflammation in the context of viral infections may be mediated by decreased activity of NK cells and their ability to clear eosinophils.